Analisis Hubungan Kepercayaan Diri, Lingkungan Belajar, dan Frekuensi Latihan terhadap Kemampuan Berbicara Bahasa Inggris - Dian Pratiwi; Inna 'Ainul Muthi'ah (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Pamulang, Indonesia, 2025)
This research aims to analyze the influence of self-confidence, learning environment, and frequency of practice on English speaking ability. The sample of the study consisted of 40 third-semester English Education students at UIN Walisongo Semarang who were enrolled in the Professional Listening & Speaking course. A questionnaire that had undergone validity and reliability tests was used to collect data. Multiple linear regression was used in this study to ascertain the simultaneous and partial effects of the three independent variables on speaking ability. The findings of the study showed that learning environment (X2), frequency of practice (X3), and self-confidence (X1) all had significant impacts on English speaking ability (Y). Learning environment and self-confidence were the next two factors that contributed the most, after frequency of practice. With an R-squared value of 94.15%, the regression model was able to account for 94.15% of the variation in English speaking ability, with 5.85% coming from characteristics not included in the model. The model met the criteria of independence, homoscedasticity, and normality, according to the residual assumption test, which confirmed the validity of the analysis findings.